Out-of-pocket expenditure and catastrophic costs due to COVID-19 in Indonesia: A rapid online survey - Firdaus Hafidz; Insan Rekso Adiwibowo; Gilbert Renardi Kusila; Mahlil Ruby; Benyamin Saut; Citra Jaya; Wan Aisyiah Baros; Dedy Revelino; Erzan Dhanalvin; Ayunda Oktavia (Frontiers Media S.A., 2023)
BackgroundThe Corona Virus Disease 2019 (COVID-19) pandemic has created a substantial socioeconomic impact, particularly in developing countries such as Indonesia.Purpose(s)/objective(s)This study aimed to describe the COVID-19-related out-of-pocket spending of Indonesian citizens and the proportion of whom experienced catastrophic health spending during the COVID-19 pandemic using the patient's perspective.MethodologyWe conducted a rapid cross-sectional online survey across provinces in Indonesia to capture participants' experiences due to COVID-19. Data were collected between September 23rd to October 7th of 2021 including demographics, income, and expenditures. Descriptive statistics were used to analyze the respondents' characteristics. Patients's perspective of total cost was estimated from out-of-pocket of COVID-19 direct costs and compared them to total expenditure. If the proportion of COVID-19 total costs exceeded 40% of the total expenditure, the respondents were deemed to have faced catastrophic costs.ResultsA total of 1,859 respondents answered the questionnaire. The average monthly income and expenditure of respondents were 800 USD, and 667 USD respectively. The monthly expenditure was categorized into food expenditure (367 USD) and non-food expenditure (320 USD). The average of COVID-19-related monthly expenditure was 226 USD, including diagnostic expenditure (36 USD), preventive expenditure (58 USD), medical expenditure (37 USD for COVID-19 treatment; and 57 USD for post-COVID-19 medical expenses), and non-medical expenditure (30 USD). Analysis showed that 18.6% of all respondents experienced catastrophic costs while 38.6% of the respondents who had COVID-19 treatment experienced catastrophic costs.ConclusionThe high proportion of catastrophic costs among respondents suggests the need for COVID-19 social protection, especially for COVID-19 diagnostic and prevention costs. The survey findings have led the government to increase the benefit coverage other than medical costs at the hospitals.